Benefits of using digital thoracic drainage systems for post-operative treatment in pediatric populations: personal experience and review of literature - Frediani, Simone; Romano, Giorgia; Pardi, Valerio; Aloi, Ivan Pietro; Bertocchini, Arianna; Accinni, Antonella; Zarfati, Angelo; Inserra, Alessandro (Frontiers in Pediatrics, 2023)
Introduction: The digital chest drainage monitoring system (Medela Thopaz+), unlike analogical systems, reliably regulates the pressure applied to the patient’s chest and digitally and silently monitors critical therapeutic indicators (volume of fluid and/or drained air). Its use in adulthood has been widely described, but there is still little experience in the pediatric field. The aim of this study is to test this new device in the pediatric population. Materials and Methods: We conducted a retrospective study of 160 patients undergoing chest surgery at our Hospital. These patients were divided into 82 treated with the Thopaz system in the period from January 2021 to April 2023 and 78 in whom Pleurevac, had been used in the time period from January 2020 to April 2023. Results: The average age of patients was 10.45 years (range: 3.1 – 17.2) for the Thopaz Group and 10.71 years for Pleurevac Group. The groups were homogeneus also by weight and type of intervention. The device was held in place for 10.64 days (mean) for Thopaz Group, compared to 16.87 days (mean) for Pleurevac Group (p<0.05). The median number of postoperative X-rays before the closure of the chest tube was 4.29 in the digital drainage group compared to 8.41 in the traditional draining group (p< 0.05). Conclusions: The digital chest monitoring device provides objective measurement, allows for rapid patient mobilization (with good pain control and increased compliance). In addition, the use of Thopaz in the paediatric population seems to be safe (there is no statistically significant difference in terms of complications such as prolonged air leaks and pneumothorax after the chest tube closure) and potentially beneficial.